Reassessing Global Innovation Metrics: Critical Analysis of GII Indicators and Intangible Investment Trends - Archil Chirakadze; Nodar Mitagvaria; Neli Makhviladze; Teimuraz Chubinishvili; Nodar Sulashvili; Deva Harsha Uday Gundluru; Giorgi Palavandishvili; Khtuna Tserodze; Kakha Gorgadze; Nana khuskivadze; David Aphkhazava (Theoretical Hypotheses and Empirical Results, 2025)
This study critically examines the reliability and validity of indicators used in calculating the Global Innovation Index (GII), while investigating emerging trends in intangible versus tangible investment patterns across developed and developing economies. Through correlation analysis of 13 development indicators across 100 countries (2021-2024), we reveal significant inconsistencies in widely-used GII metrics across different economic development groups. Our findings demonstrate that several conventional innovation indicators fail to correlate appropriately within specific country clusters, potentially compromising the accuracy of global innovation assessments. Simultaneously, analysis of the World Intellectual Property Organization’s (WIPO) 2025 World Intangible Investment Highlights reveals that intangible investment has grown 3.7 times faster than tangible investment between 2008-2024, reaching USD 7.6 trillion in 2024. This research identifies critical gaps in current innovation measurement methodologies and provides evidence-based recommendations for refining GII calculation methods. The study emphasizes the need for rigorous indicator validation, incorporation of sustainable development metrics, and recognition of the growing dominance of intangible assets in driving economic innovation. Our results suggest that continued reliance on unvalidated indicators may lead to systematic misassessment of national innovation capabilities, with implications for policy-making and resource allocation in the global knowledge economy.